2011
DOI: 10.1007/s12160-011-9297-6
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and Pain Sensitivity: Findings from Female Twins

Abstract: Background Systemic inflammation and pain sensitivity may contribute to the development and maintenance of chronic pain conditions. Purpose We examined the relationship between systemic inflammation as measured by C-reactive protein (CRP), and cold pain sensitivity in 198 female twins from the University of Washington Twin Registry. We also explored the potential role of familial factors in this relationship. Methods Linear regression modeling with generalized estimating equations examined the overall and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 20 publications
5
42
0
Order By: Relevance
“…The device was a 12-L container filled with water and ice maintained at 1–2 degrees Celsius by constant circulation with an internal pump [24]. Participants were asked to immerse their non-dominant hand in the water up to the wrist.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The device was a 12-L container filled with water and ice maintained at 1–2 degrees Celsius by constant circulation with an internal pump [24]. Participants were asked to immerse their non-dominant hand in the water up to the wrist.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked to withdraw their hand when the pain became intolerable; latency from hand immersion to hand withdrawal was recorded as CPT Immersion Tolerance . We also calculated participants’ latency to hand withdrawal following indication of pain onset by subtracting Pain Threshold from Immersion Tolerance; this parameter has been conceptualized as participants’ ability to tolerate actual pain experience associated with the CPT and was recorded as CPT Pain Tolerance [24]. Finally, participants were asked to rate their pain intensity at three time points during the procedure – at the point they indicated pain onset (CPT Threshold Pain Rating), when they withdrew their hand from the CPT (CPT Immersion Tolerance Pain Rating), and at 15 minutes following hand withdrawal (CPT Delayed Pain Rating) .…”
Section: Methodsmentioning
confidence: 99%
“…Members of the registry were selected from the UWTR to participate in a study examining psychological, behavioral, and physiological risk factors for medically unexplained chronic pain between 2006 to 2010. The rationale for the study, its methodology, and other outcomes have been previously reported (1517). Because the study was focused on examining correlates of medically unexplained chronic pain, exclusion criteria included medical conditions such as autoimmune diseases or cancer that could account for the presence of pain and any medical conditions like uncontrolled allergies or endocrine conditions, heart and lung problems, and sleep disorders that could alter data collection.…”
Section: Methodsmentioning
confidence: 99%
“…The study also involved at-home collection of saliva samples and a two-day laboratory session at the University of Washington General Clinical Research Center for physical examinations and other study tasks, which are not included in the present analyses but are reported elsewhere (1517). Participants were asked to avoid taking all medications that might impact sleep, pain, the hypothalamic-pituitary-adrenal (HPA) axis, or the autonomic nervous system during the study period and for the two weeks prior to the study.…”
Section: Methodsmentioning
confidence: 99%
“…healthy control pairs). As reported previously (42, 43), in order to participate, both twins were required to be free from severe or chronic medical conditions that could potentially be the source of the unexplained pain (e.g. autoimmune disorders, cancer, etc.…”
Section: Methodsmentioning
confidence: 99%